Creating A Safe Environment: The Role of Safeguarding Workshops In Protecting Vulnerable Groups - Ekorini Listiowati; Farindira Rahmasari; Yuanita Wulandari; Husnan Nurjuman; Yuyun Pramayanti; Agus Samsudin; Dirwan Soularto (International Journal Of Community Service, 2025)
Safeguarding is a critical component of healthcare services, particularly as it relates to protecting vulnerable populations. It aims to shield individuals from violence, exploitation, sexual abuse, and neglect. The concept of safeguarding goes beyond physical protection, encompassing psychological, social, and legal dimensions that uphold individual rights—especially for vulnerable groups such as children, women, persons with disabilities, and those with limited access to safe healthcare services. This community engagement initiative aimed to raise awareness and understanding of safeguarding and risk mitigation in healthcare services. The safeguarding workshop involved participants from Muhammadiyah organizations and utilized group discussions, case studies, role-plays, and scenario-based simulations. Pre- and post-training evaluations were conducted to assess the increase in participant understanding. The results indicated an improvement in safeguarding knowledge and led to the drafting of the initial Safeguarding Guidelines for Health Council of Muhammadiyah Central Board. These guidelines encompass safeguarding definitions, core principles, preventive strategies, case-handling procedures for violence, exploitation, and sexual abuse (VESA), and reporting mechanisms tailored to Muhammadiyah’s context. iven the novelty of safeguarding as a concept, some participants found it challenging to identify forms of VESA or understand preventive measures. Thus, continued efforts through advanced training and broader policy dissemination are necessary to deepen understanding and enhance implementation. Safeguarding is a critical component of healthcare services, particularly as it relates to protecting vulnerable populations. It aims to shield individuals from violence, exploitation, sexual abuse, and neglect. The concept of safeguarding goes beyond physical protection, encompassing psychological, social, and legal dimensions that uphold individual rights—especially for vulnerable groups such as children, women, persons with disabilities, and those with limited access to safe healthcare services. This community engagement initiative aimed to raise awareness and understanding of safeguarding and risk mitigation in healthcare services. The safeguarding workshop involved participants from Muhammadiyah organizations and utilized group discussions, case studies, role-plays, and scenario-based simulations. Pre- and post-training evaluations were conducted to assess the increase in participant understanding. The results indicated an improvement in safeguarding knowledge and led to the drafting of the initial Safeguarding Guidelines for Health Council of Muhammadiyah Central Board. These guidelines encompass safeguarding definitions, core principles, preventive strategies, case-handling procedures for violence, exploitation, and sexual abuse (VESA), and reporting mechanisms tailored to Muhammadiyah’s context. iven the novelty of safeguarding as a concept, some participants found it challenging to identify forms of VESA or understand preventive measures. Thus, continued efforts through advanced training and broader policy dissemination are necessary to deepen understanding and enhance implementation.